Recurrent preauricular fistula surgery guided by fistulography - Dini Widiarni Widodo; Raden Ayu Anatriera; Astika Pramesti Tunggadewi; Reyhan Eddy Yunus (Elsevier, 2022)
Recurrent infection in a preauricular fistula is an indication for surgery. The proper surgical technique minimizes complications and recurrence in cases of preauricular fistula. Two cases with a complaint of recurrent discharge from the hole in the front of the ear accompanied by redness and pain. Physical and supporting examinations support the diagnosis of a preauricular fistula. Supraauricular and synectomy approaches are two commonly applied surgical techniques, but various procedures can be performed.